2021
DOI: 10.5435/jaaos-d-20-00210
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Durotomy in Lumbar Spine Surgery; Risk Factors, Complications, and Perioperative Management

Abstract: Incidental durotomy (ID) can occur in up to 14% of all lumbar spine surgeries. The risk of this complication is markedly higher among elderly patients with advanced spinal pathology. In addition, revision cases and other more invasive procedures increase the risk of ID. When unrepaired, IDs can increase the risk of developing meningitis and can lead to the formation of cerebrospinal fluid fistulas and pseudomeningoceles. Intraoperative recognition and repair are essential to ID management, although repair tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Our data showed no effect on CSFL development, suggesting a generally safe applicability with reduced or no force of suction. It does not allow further conclusions such as previous reports advocating for epidural drainage placement in order to reduce the risk of CSFL by influencing epidural pressure gradients and thus supporting wound healing (16,20). Furthermore, our results are inconsistent with reports of increased complication rates, including CSFL, following epidural drainage in both planned and accidental durotomy (3,(21)(22)(23)(24).…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Our data showed no effect on CSFL development, suggesting a generally safe applicability with reduced or no force of suction. It does not allow further conclusions such as previous reports advocating for epidural drainage placement in order to reduce the risk of CSFL by influencing epidural pressure gradients and thus supporting wound healing (16,20). Furthermore, our results are inconsistent with reports of increased complication rates, including CSFL, following epidural drainage in both planned and accidental durotomy (3,(21)(22)(23)(24).…”
Section: Discussioncontrasting
confidence: 94%
“…Use of fibrin sealants has been discouraged by several authors following both planned and unplanned durotomies due to a lack of effectiveness in preventing CSFL ( 10 , 14 16 ), even though two studies reported favorable results ( 4 , 17 ). The effectiveness and the necessity of patch sealants to prevent CSFL are not sufficiently studied in planned durotomies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidental durotomy (ID) identification. Incidental durotomy (ID) is a common intra-operative complication during spine surgery, occurring up to 14% of lumbar spine surgeries [ 29 ]. It is defined as an inadvertent tearing of the dura during surgery with cerebrospinal fluid (CSF) extravasation or bulging of the arachnoid [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acute thromboembolic illness (VTE) may result in substantial morbidity, poor quality of life, and even death [ 3 ]. It may also lead to increased medical costs and a considerable financial burden on individuals and their families [ 4 ]. The use of pharmacological prophylaxis is well established in a variety of surgical procedures, most notably hip and knee replacements, for which there are well-established criteria and dosing guidelines [ 5 ].…”
Section: Introductionmentioning
confidence: 99%